11
$\begingroup$

This is question 3 from the APICS Mathematics Competition paper of 1999:

Prove that $$\sin^2(x+\alpha)+\sin^2(x+\beta)-2\cos(\alpha-\beta)\sin(x+\alpha)\sin(x+\beta)$$ is a constant function of $x$.

Expanding it seems rather daunting, in particular the last term, and nothing I've tried has been useful towards cancelling terms out. It was assigned in a pre-calculus course, so it should be possible to solve without using derivatives. However, showing that $f'(x)=0$ would obviously be a valid solution.

Any ideas are greatly welcome.

$\endgroup$
  • 1
    $\begingroup$ The natural idea would be to rewrite it in terms of complex exponentials and simplify. $\endgroup$ – Carl Mummert Jul 24 '16 at 14:30
  • 6
    $\begingroup$ My gut feeling says think in terms of law of cosines. $\endgroup$ – Siong Thye Goh Jul 24 '16 at 14:34
  • $\begingroup$ Differentiating, you get a trig identity whose proof is really no simpler than the original. $\endgroup$ – DanielWainfleet Jul 24 '16 at 21:31
  • 1
    $\begingroup$ Rewriting everything in terms of $\sin(x)=\frac{1}{2i}(e^{ix}-e^{-ix})$ and $\cos(x)=\frac{1}2(e^{ix}+e^{-ix})$ is a trick that always works for this sort of problem. Not so elegant and maybe less comfortable for "pre-calculus", but if someone puts this problem in front of me, that's what's going to happen. $\endgroup$ – Milo Brandt Jul 25 '16 at 3:47
17
$\begingroup$

enter image description here

Taking @SiongthyeGoh's comment, in the above picture, $AE=1$, $\angle BAE=x$, $\angle BAC=\beta$, and $\angle BAD=\alpha$.

It follows that $DE=\sin(x+\alpha)$ and $CE=\sin(x+\beta)$. Applying the cosine theorem to $\triangle DCE$, the given expression is equal to $DC^2$, hence is a constant.

$\endgroup$
  • $\begingroup$ Quick question: I can see how the given expression is equal to $DC^2$. However, how do we know that $DC$ is constant as the angle x varies? $\endgroup$ – user200783 Jul 25 '16 at 11:02
  • 2
    $\begingroup$ $DC$ spans an arc of $2(\alpha-\beta)$ of the circle with diameter $AB=1$. $\endgroup$ – Quang Hoang Jul 25 '16 at 15:13
8
$\begingroup$

Let $$E=\sin^2(x+\alpha)+\sin^2(x+\beta)-\color {blue}{2\cos(\alpha-\beta)\sin(x+\alpha)}\sin(x+\beta)$$

Now use $2\cos A \sin B = \sin (A+B) - \sin (A-B)$.

$$E=\sin^2(x+\alpha)+\sin^2(x+\beta)-\left[\sin\left(\alpha-\beta +x+\alpha\right)-\sin\left(\alpha-\beta -x-\alpha\right)\right]\sin(x+\beta)$$

$$E=\sin^2(x+\alpha)+\sin^2(x+\beta)-\left[\sin\left(\alpha-\beta +x+\alpha\right)-\sin\left(-\beta -x\right)\right]\sin(x+\beta)$$

$$E=\sin^2(x+\alpha)+\sin^2(x+\beta)-\left[\sin\left(\alpha-\beta +x+\alpha\right)+\sin\left(x+\beta \right)\right]\sin(x+\beta)$$

$$E=\sin^2(x+\alpha)-\color {red}{\sin\left(\alpha-\beta +x+\alpha\right)\sin(x+\beta)}$$

Now use $2\sin A \sin B = \cos (A-B) - \cos (A+B)$.

$$E=\sin^2(x+\alpha)-\frac{1}{2}\left[\cos(2\alpha-2\beta)-\cos(2x+2\alpha)\right]$$

$$E=\sin^2(x+\alpha)-\frac{1}{2}\cos(2\alpha-2\beta)+\frac{1}{2}\color{green}{\cos(2x+2\alpha)}$$

$$E=\sin^2(x+\alpha)-\frac{1}{2}\cos(2\alpha-2\beta)+\frac{1}{2}\left[1-2\sin^2(x+\alpha)\right]$$

$$E=\frac{1}{2}-\frac{1}{2}\cos(2\alpha-2\beta)$$

$\endgroup$
4
$\begingroup$

$$F=\sin^2(x+\alpha)+\sin^2(x+\beta)-2\cos(\alpha-\beta)\sin(x+\alpha)\sin(x+\beta)$$

$$=1-\{\underbrace{\cos^2(x+\alpha)-\sin^2(x+\beta)}\}-\cos(\alpha-\beta)\{\underbrace{2\sin(x+\alpha)\sin(x+\beta)}\}$$

Using Prove that $\cos (A + B)\cos (A - B) = {\cos ^2}A - {\sin ^2}B$ and Werner Formula$(2\sin A\sin B=\cdots),$ $$D=1-\cos(2x+\alpha+\beta)\cos(\alpha-\beta)-\cos(\alpha-\beta)[\cos(\alpha-\beta)-\cos(2x+\alpha+\beta)]$$

$$=\cdots=1-\cos^2(\alpha-\beta)$$ which is independent of $x$

$\endgroup$
4
$\begingroup$

HINT

Use the formulas $\sin^2t=\frac {1-\cos2t} 2$ and $\cos2p+\cos2q=2\cos(p+q)\cos(p-q)$.

$\endgroup$
3
$\begingroup$

$$\text {Let }\quad L=\sin^2 (x+a)+\sin^2(x+b).$$ $$\text {Let }\quad R=-2\cos (a-b)\sin (x+a) \sin (x+b).$$ $$\text {We have }\quad L=\frac {1}{2}(1-\cos (2x+2a) +\frac {1}{2}(1-\cos (2x+2b).$$ Now with $y=2x+a+b$ and $z=a-b$ we have $$\cos (2x+2a)=\cos (y+z)=\cos y \cos z-\sin y \sin z. $$ $$\cos (2x+2b)=\cos (y-z)=\cos y \cos z +\sin y \sin z .$$ $$\text {Thus, }\quad\cos (2x+2a) + \cos (2x+2b )=2 \cos y \cos z.$$ $$\text {Therefore }\quad L=1-\cos y \cos z.$$ The motivation for this comes from examining R : We always have $\sin U \sin V= \frac {1}{2}(\cos (U-V)-\cos (U+V)). $ So we have $$\sin (x+a) \sin (x+b)=\frac {1}{2}(\cos (a-b)-\cos (2x+a+b))=\frac {1}{2}(\cos z-\cos y).$$ $$\text {Therefore }\quad R= (-2\cos z)\cdot \frac {1}{2}(\cos z-\cos y)=-\cos^2 z+\cos z \cos y.$$ $$\text {In conclusion, } \quad L+R=1-\cos^2z=1-\cos^2 (a-b)$$ which is independent of $x.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.